Revision of the genus Diochus Erichson (Coleoptera: Staphylinidae, Staphylininae, Diochini) from Indonesia, Malaysia and Singapore - Huang, Tian; Janák, Jiří; Zhou, Hong-Zhang (Zootaxa, 2025)
The taxonomy of the genus Diochus Erichson, 1839 (Coleoptera: Staphylinidae, Staphylininae, Diochini) was studied in this paper. Eight new species are described: Diochus acehensis Huang, Janák & Zhou, sp. nov., D. bogorensis Huang, Janák & Zhou, sp. nov., D. lombokensis Huang, Janák & Zhou, sp. nov., D. paradoxus Huang, Janák & Zhou, sp. nov., D. paraparadoxus Huang, Janák & Zhou, sp. nov., D. sulawesiensis Huang, Janák & Zhou, sp. nov. and D. uvellipticus Huang, Janák & Zhou, sp. nov. from Indonesia; D. parellipticus Huang, Janák & Zhou, sp. nov. from Malaysia. Four previously described species are revised here: D. borneensis Cameron, 1933, D. punctipennis (Motschulsky, 1858), D. antennatus (Motschulsky, 1858) and D. pulchellus Cameron, 1918. A key to all 12 species is provided and all new species are illustrated.